Perinatal Outcome of Previable Premature Rupture of Membranes Before 24 Weeks of Gestation: A Single-Centered Retrospective Cohort Study - Dogan, Yasemin; Kockaya, Ercan; Eser, Muzeyyen Dilsad; Gunlemez, Ayla (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Preterm premature rupture of membranes (PPROM) has unfavorable consequences for the neonate and the mother if it occurs before 24 weeks of gestation. We aim to present our series to elucidate the course of previable PPROM and to detect maternal and neonatal outcomes. STUDY DESIGN: A single-centered retrospective cohort study that involves singleton patients diagnosed with spontaneous PPROM before 24 weeks. Data were retrieved from medical records, and maternal and neonatal outcomes were noted. RESULTS: Seventy-eight women were diagnosed with PPROM before 24 weeks, 42 patients (54%) opted for termination of pregnancy, and seven patients (9%) had spontaneous abortion. Twentynine patients (37%) gave live birth after a median latency of 47 days. Neonatal complications were respiratory distress syndrome (n=19; 65%), early sepsis (n=10; 34%), late sepsis (n=5; 17%), bronchopulmonary dysplasia (n=5;17%), retinopathy of prematurity (n=3; 10%), pneumothorax (n=5; 17%), intracranial hemorrhage (n=2; 6%), necrotizing enterocolitis (n=1; 3%) and meningitis (n=1; 3%). In the liveborn group, the neonatal survival rate was 62%. Of the survivors, twelve babies (66%) were discharged without composite neonatal morbidity. Maternal complications in the expectant management group included clinical chorioamnionitis (n=12, 33%) and placental abruption (n=2, 5%). CONCLUSION: In previable PPROM, overall half of the babies survive after expectant management. While a prolonged latency period and subsequent delivery at advanced gestational ages improve neonatal outcomes, such a conservative approach poses a substantial risk for chorioamnionitis.